ConTEdb: a comprehensive database of transposable elements in conifers. (17th December 2018) - Yi, Fei; Ling, Juanjuan; Xiao, Yao; Zhang, Hanguo; Ouyang, Fangqun; Wang, Junhui
Abstract: Conifers are the largest and most ubiquitous group of gymnosperms and have significant ecological significance and economic importance. However, the huge and complex genomes have hindered the sequencing and mining of conifer genomes. In this study, we identified 413 423 transposable elements (TEs) from Picea abies, Picea glauca and Pinus taeda using a combination of multiple approaches and classified them into 11 133 families. A comprehensive web-based database, ConTEdb, was constructed and served for researchers. ConTEdb enables users to browse, retrieve and download the TE sequences from the database. Several analysis tools are integrated into ConTEdb to help users mine the TE data easily and effectively. In summary, ConTEdb provides a platform to study TE biology and functional genomics in conifers.